Conductive polymer electrolyte for battery

A porous film-based solid polymer electrolyte with a thermoplastic polymer and ionically conductive oligomer addresses low temperature conductivity and mechanical instability issues, ensuring stable battery operation and safety.

JP2025000601AInactive Publication Date: 2025-01-07ARKEMA FRANCE SA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024140716
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-11-30
Filing Date
2024-08-22
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing solid polymer electrolytes used in lithium batteries suffer from low ionic conductivity at low temperatures, mechanical instability, and flammability due to high molecular mass and residual monomers, limiting their use to temperatures above 60°C and reducing their safety and flexibility.

Method used

A solid polymer electrolyte composed of a semi-crystalline thermoplastic polymer in the form of a porous film impregnated with an ionically conductive oligomer and lithium salts, produced through a simple method involving solvent and non-solvent evaporation, ensuring high ionic conductivity and mechanical stability at temperatures below 60°C.

Benefits of technology

The electrolyte maintains high ionic conductivity and mechanical stability at low temperatures, allowing for safe and flexible battery operation, with a simple and cost-effective production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000601000001
    Figure 2025000601000001
  • Figure 2025000601000002
    Figure 2025000601000002
Patent Text Reader

Abstract

To provide a solid polymer electrolyte which has satisfactory ion conductivity even at low temperature, below 60°C, and which may go down to -20°C.SOLUTION: There is provided an electrolyte which is a solid polymer electrolyte intended to be used in a battery functioning at a temperature below 60°C. The electrolyte contains: a thermoplastic polymer that is in the form of a porous film and has a molecular mass of greater than 50,000 g / mol, the thermoplastic polymer being a P(VDF-TrFE) copolymer in which the VDF / TrFE molar ratio of structural units ranges from 9 to 0.1, or a P(VDF-TrFE-CTFE) terpolymer in which the molar content of VDF ranges from 40% to 95%, the molar content of TrFE ranges from 5% to 60% and the molar content of CTFE ranges from 0.5% to 20%; an oligomer which impregnates a film of the thermoplastic polymer, the oligomer being an ion conductor; and one or more lithium salts. The electrolyte has an ion conductivity of at least 0.1 mS / cm at 25°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of lithium batteries, and more particularly to lithium polymer batteries and batteries known as "all-solid-state" batteries, which may contain alkali metal cations such as Na or Li, alkaline earth metal cations such as Ca or Mg, or finally aluminum in the electrolyte.

[0002] More particularly, the invention relates to a solid polymer electrolyte in the form of an organic-organic composite intended for use in such batteries. The invention also relates to a method for producing such an electrolyte, which is particularly intended for making lithium polymer batteries or "all-solid-state" batteries, especially those involving ionically conductive separators. The invention therefore also relates to battery separators comprising such polymer electrolytes, methods for their manufacture, and batteries incorporating such electrolytes. [Background technology]

[0003] Conventional lithium-ion batteries contain a solvent and a flammable liquid electrolyte based on lithium salts. Given the increasing use of this type of battery in the field of electronic consumer products such as computers, tablets or mobile phones (smartphones), but also in the field of transportation, especially electric vehicles, it is a major challenge to improve the safety of these lithium batteries and to reduce their manufacturing costs.

[0004] To solve this problem, lithium polymer batteries containing solid polymer electrolytes (also known as SPEs) to replace flammable liquid electrolytes have been researched in recent years. Thus, solid polymer electrolyte SPEs, which do not contain liquid solvents, avoid the use of flammable liquid components as in conventional Li-ion batteries, allowing the production of thinner and more flexible batteries.

[0005] Despite their low intrinsic ionic conductivity, SPEs show great potential for both small-scale applications, e.g., three-dimensional microbatteries, and large-scale energy storage applications, e.g., electric vehicles.

[0006] Currently, the polymers most commonly used as solid polymer electrolytes are polyethers, such as poly(ethylene oxide), also known as PEO. However, these polymers have the drawback of easily crystallizing, especially at temperatures close to room temperature, which has the effect of very significantly reducing the ionic conductivity of the polymer. For this reason, the use of batteries intercalated with these polymers is only possible at a minimum temperature of 60° C. However, it would be advantageous to be able to use such batteries at room temperature and even at negative temperatures. Furthermore, these PEOs are highly hydrophilic and tend to plasticize, especially in the presence of lithium salts, reducing their mechanical stability.

[0007] Aliphatic polycarbonates have also been investigated as host polymer matrices for SPE. To this end, cyclic carbonates can be polymerized by ring opening to produce linear polymeric carbonates in solid form. Such ethylene carbonate polymers can be used to transport lithium ions, Li + Although they have been prepared and used successfully as electrolytes for conducting hydrogen, the stability of five-membered cyclic carbonates such as ethylene carbonate makes them less than ideal candidates for controlled polymerization, since the polymerization of ethylene carbonate is accompanied by decarboxylation, resulting in copolymers of carbonate and ethylene oxide. [G. Rokicki et al., Prog. Polym. Sci. 25 (2000) 259-342].

[0008] The article by D. Brandell, Solid State Ionics 262 (2014) 738-742, describes the preparation by bulk polymerization of poly(trimethylene carbonate), also known as PTMC, by ring opening of trimethylene carbonate (TMC) monomer initiated with tin dioctanoate. The polymer obtained has a molecular mass of 368000 g / mol, a polydispersity of 1.36 and contains less than 7% residual monomer. Such polymers are amorphous and have a relatively low glass transition temperature of -15 °C. Similarly, the article published in the Journal of Power Sources 298 (2015) 166-170, D. Brandell et al., also describes the copolymerization of caprolactone with trimethylene carbonate, which makes it possible to obtain amorphous ionically conductive polymers with a low glass transition temperature of -63.7 °C. However, the polymers described in these documents are still dangerous for use as solid polymer electrolytes for batteries. This is because there is a risk of flammability if there is a high amount of residual monomer. Finally, the polymers described in these two documents have a number-average molecular mass much higher than 100,000 g / mol, in order to avoid problems with mechanical stability, especially in the electrode, so that they do not come off the metal current collector. However, the higher the molecular mass of the polymer, the more detrimental this is for its chain mobility and its ionic conductivity.

[0009] A controlled, living, selective polymerization method has further been developed that makes it possible to obtain polyesters and polycarbonates, which may or may not be copolymerized, via organic catalysts, where the organic catalysts are organic, such as MSA (methanesulfonic acid) or TfOH (trifluoromethanesulfonic acid), i.e. the polymerization is carried out without the introduction of metal derivatives, such as tin salts.

[0010] Methanesulfonic acid (MSA) has proven to be highly efficient in the polymerization of ε-caprolactone (ε-CL) or trimethylene carbonate (TMC), and trifluoromethanesulfonic acid (TfOH) is the organocatalyst of choice to carry out the controlled polymerization of β-butyrolactone (BBL).

[0011] WO2008 / 104723 and WO2008 / 10472, as well as the article entitled "Organo-catalyzed ROP of ε-caprolactone: methanesulfonic acid competes with trifluoromethanesulfonic acid", Macromolecules, 2008, volume 41, pages 3782-3784, in particular, have demonstrated the efficiency of methanesulfonic acid as a catalyst for the polymerization of ε-caprolactone. Said document also describes that MSA, in combination with a protic initiator of the alcohol type, can promote the controlled polymerization of ε-caprolactone cyclic monomers. In particular, the protic initiator allows for precise control of the average molar mass and the chain ends.

[0012] Oligomers with high ionic conductivity are known, but they do not have the mechanical strength. A low glass transition temperature (Tg) is sought to improve the electrical conductivity, but this comes at the expense of the mechanical properties. Conversely, if they are better, it is because the molar mass has increased or the polymer shows crystallinity.

[0013] The Applicant therefore sought a solution to prepare solid polymer electrolytes with sufficient ionic conductivity at low temperatures, i.e. room temperature, and even at negative temperatures, typically between +60°C and -20°C, and to do this, chose to separate the mechanical and conductive functions. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] International Publication No. 2008 / 104723 [Patent Document 2] International Publication No. 2008 / 10472 [Non-patent literature]

[0015] [Non-Patent Document 1] G. Rokicki et al., Prog. Polym. Sci. 25 (2000) 259-342 [Non-Patent Document 2] D.Brandell,Solid State Ionics 262(2014)738-742 [Non-Patent Document 3] the Journal of Power Sources 298(2015)166-170, D. Brandell et al. [Non-Patent Document 4] “Organo-catalyzed ROP of ε-caprolactone:methanesulfonic acid competes with trifluoromethanesulfonic acid”, Macromolecules, 2008, volume 41, pages 3782-3784 Summary of the Invention [Problem to be solved by the invention]

[0016] The object of the present invention is therefore to overcome at least one of the drawbacks of the prior art, and is particularly directed to the proposal of a solid polymer electrolyte having sufficient ionic conductivity even at low temperatures below 60° C., and which may even go down to −20° C.

[0017] To do this, the conductive portion of the electrolyte must have as little crystallinity as possible and a glass transition temperature below the intended operating temperature of the battery. The polymer electrolyte material must also allow for the preparation of electrodes that provide good particle cohesion and good adhesion to the current collector.

[0018] The polymer electrolyte material must also enable the preparation of a separator that has sufficient electrochemical stability (potential depending on the cathode material used) and sufficient ionic conductivity over the anticipated operating temperature range.

[0019] The present invention is also directed to proposing methods for the synthesis of such materials that are fast, simple and inexpensive to carry out. [Means for solving the problem]

[0020] According to a first aspect, the invention relates to a solid polymer electrolyte intended for use in a battery operating at a temperature below 60° C., comprising: - thermoplastic polymers in the form of porous films having a molecular mass of more than 50000 g / mol; an oligomer, which is an ion conductor, impregnating the film of said thermoplastic polymer; and one or more lithium salts, The present invention relates to an electrolyte comprising:

[0021] According to one embodiment, the thermoplastic polymer has the general formula: -[(CR1R2-CR3R4)-] n (wherein R1, R2, R3 and R4 are independently H, F, CH3, Cl, Br or CF3, and it is understood that at least one of these groups is F or CF3).

[0022] According to one embodiment, the thermoplastic polymer is characterized by piezoelectric, ferroelectric, pyroelectric or relaxor ferroelectric properties.

[0023] The thermoplastic polymer contained in the solid polymer electrolyte composition is prepared in the form of a porous film.

[0024] The method for preparing the porous film comprises the steps of: providing an ink comprising a thermoplastic polymer and a vehicle comprising a solvent for said polymer and a non-solvent for said polymer, said solvent being mutually miscible; - depositing said ink onto a substrate; - Evaporating the vehicle including the solvent and the non-solvent.

[0025] The solid polymer electrolyte according to the present invention comprises an oligomer impregnated into a film of a thermoplastic polymer, according to one embodiment, the ion-conducting oligomer having at least one group that has a physical or chemical affinity with the thermoplastic polymer.

[0026] The present invention also relates to a separator for a lithium polymer battery, characterized in that it contains the above-mentioned solid polymer electrolyte.

[0027] Another subject of the invention is a lithium polymer battery comprising a separator based on a solid polymer electrolyte as defined above, placed between an anode made of lithium metal and a cathode.

[0028] According to another aspect, the invention relates to a lithium battery comprising a stack of layers, characterized in that said stack comprises an anode predominantly made of lithium metal, a cathode and a separator, said separator comprising the solid polymer electrolyte described above.

[0029] The present invention makes it possible to overcome the drawbacks of the prior art and, more particularly, to provide a solid polymer electrolyte that has sufficient ionic conductivity even at low temperatures.

[0030] This is achieved by the implementation of an organic-organic composite polymer material consisting of a porous film of a semi-crystalline thermoplastic polymer impregnated with an ion-conducting oligomer having at least one functional group with affinity for the thermoplastic polymer.

[0031] This type of polymer electrolyte is prepared according to a very simple, rapid and cheap method, which involves merely dissolving, drying and impregnation operations which can be carried out at very mild temperatures.

[0032] The ionic conductivity of a polymer electrolyte is proportionally higher when the measurement is performed at a higher temperature, away from the glass transition temperature of the thermoplastic polymer. The fact that the thermoplastic polymer backbone allows the maintenance of mechanical strength leads to a decoupling of the conduction and mechanical strength (mechanical modulus) functions.

[0033] The solid polymer electrolyte of the present invention ensures mechanical stability during the charge-discharge cycles of the battery and allows the electrode to maintain cohesion during the volume fluctuations associated with lithium insertion / deinsertion, without compromising ionic conductivity due to excessively long chains. Up until now, to solve this size stability problem, especially with PEO, it was necessary to produce polymers with very long chains to ensure mechanical stability of the electrode. However, this increase in the molecular mass of the polymer comes at the expense of its chain mobility and its ionic conductivity.

[0034] Considering the mechanical and conduction functions in isolation, these considerations appear to pose no further limitations. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] The invention is described in further detail below.

[0036] The present invention relates to a solid polymer electrolyte intended for use in a battery operating at a temperature below 60° C., comprising: a thermoplastic polymer in the form of a porous film having a molecular mass of more than 50 000 g / mol; an oligomer, which is an ion conductor, to be impregnated into the film of said thermoplastic polymer; and one or more lithium salts, The present invention relates to an electrolyte comprising:

[0037] Thermoplastic polymer film The term "polymer" refers to a macromolecule consisting of a sequence of one or more monomers connected together through covalent bonds. The term is used herein to encompass homopolymers, copolymers consisting of two different constitutional units, and copolymers consisting of three or more different constitutional units. The term "thermoplastic polymer" as used herein refers to a polymer that becomes flowable, liquid or pasty fluid when heated and can assume new shapes by the application of heat and pressure. The thermoplastic polymers of the present invention may be amorphous or semi-crystalline.

[0038] Advantageously, the thermoplastic polymer has good mechanical properties and is capable of being crosslinked. The term "good mechanical properties" means a Young's modulus of at least 1 MPa, preferably at least 10 MPa, at the maximum operating temperature.

[0039] The thermoplastic polymer has a number average molecular mass of more than 50000 g / mol. According to one embodiment, the thermoplastic polymer has a number average molecular mass of more than 100000 g / mol, preferably more than 200000 g / mol. The molecular weight can also be evaluated by measuring the melt flow index (10 min) at 230° C. under a load of 10 kg according to ASTM D 1238 (ISO 1133). The MFI measured under these conditions can be between 0.2 and 20 g / 10 min, preferably between 0.5 and 10 g / 10 min.

[0040] According to one embodiment, the thermoplastic polymer has the general formula: -[(CR1R2-CR3R4)-] n (wherein R1, R2, R3 and R4 are independently H, F, CH3, Cl, Br or CF3, and it is understood that at least one of these groups is F or CF3).

[0041] According to one embodiment, the thermoplastic polymer is a homopolymer of the monomer -(CR1R2-CR3R4)-. According to one embodiment, the thermoplastic polymer is a homopolymer of the following: [-(CH2-CF2)-] n It is.

[0042] According to one embodiment, the thermoplastic polymer is a copolymer having two different constitutional units, or a terpolymer having three different constitutional units, or a copolymer having four or more different constitutional units, including units derived from the monomer and units derived from at least one other comonomer. These copolymers having at least two different constitutional units are random or block copolymers. In the following text, the term "copolymer" is used to indicate any copolymer consisting of at least two different constitutional units.

[0043] According to one embodiment, the fluoropolymer is a polymer comprising units derived from vinylidene fluoride (VDF) and units derived from at least one other monomer of formula CX1X2=CX3X4, where each group in X1, X2, X3 and X4 is independently selected from H, Cl, F, Br, I and an alkyl group, optionally partially or fully halogenated, containing 1 to 3 carbon atoms, preferably the fluoropolymer comprises units derived from vinylidene fluoride and units derived from at least one other monomer of formula CX1X2=CX3X4, where each group in X1, X2, X3 and X4 is independently selected from H, Cl, F, Br, I and an alkyl group, optionally partially or fully halogenated, containing 1 to 3 carbon atoms, preferably the fluoropolymer comprises units derived from vinylidene fluoride and units derived from at least one other monomer of formula CX1X2=CX3X4, such as trifluoroethylene (TrFE), tetrafluoroethylene, chlorotrifluoroethylene (CTFE), 1,1-chlorofluoroethylene, hexafluoropropene, 3,3,3-trifluoroethylene, ... and units derived from at least one monomer selected from fluoropropene, 1,3,3,3-tetrafluoropropene, 2,3,3,3-tetrafluoropropene, 1-chloro-3,3,3-trifluoropropene and 2-chloro-3,3,3-trifluoropropene, and more preferably the fluoropolymer is selected from poly(vinylidene fluoride-co-hexafluoropropene), poly(vinylidene fluoride-co-trifluoroethylene), poly(vinylidene fluoride-ter-trifluoroethylene-ter-chlorotrifluoroethylene), and poly(vinylidene fluoride-ter-trifluoroethylene-ter-1,1-chlorofluoroethylene).

[0044] Preferably, the thermoplastic polymer or copolymer is semi-crystalline having a crystallinity between 10% and 90%, preferably between 20% and 70%.

[0045] According to one embodiment, these thermoplastic polymers are characterized by having piezoelectric, ferroelectric, pyroelectric or relaxor ferroelectric properties.

[0046] According to one embodiment, such a polymer is a P(VDF-TrFE) copolymer, the VDF / TrFE molar ratio of the structural unit being between 9 and 0.1, preferably between 4 and 1.

[0047] A preferred example of a copolymer is one of the formula P(VDF-TrFE), having a molar composition of 80 / 20 and a relative dielectric constant of the order of 9-12, measured at a frequency of 1 kHz and at room temperature.

[0048] According to another embodiment, such a polymer is a P(VDF-TrFE-CTFE) terpolymer with a molar VDF content in the range of 40% to 95%, a molar TrFE content in the range of 5% to 60% and a molar CTFE content in the range of 0.5% to 20%.

[0049] A preferred example of a terpolymer is one having a molar composition of 65 / 31 / 4, a melting point (mp) of 130° C. and a relative dielectric constant equal to 60 at 50° C. and 1 kHz.

[0050] The thermoplastic polymer contained in the solid polymer electrolyte composition is prepared in the form of a porous film. This can be done by several techniques, but the applicant favors the solvent / non-solvent route.

[0051] The manufacture of the porous film of the present invention comprises the following steps: providing an ink comprising a thermoplastic polymer and a vehicle comprising a solvent for said polymer and a non-solvent for said polymer, said solvent being mutually miscible; - depositing said ink onto a substrate; - Evaporating the vehicle including the solvent and the non-solvent.

[0052] These last two steps are carried out at or close to room temperature until a solid film is formed. The deposition or coating methods are preferably coating carried out by centrifugation (spin coating), spraying or atomization (spray coating), in particular by coating with a bar or film spreader (bar coating), coating with a slot die (slot die coating), immersion (dip coating), roll printing (roll-to-roll printing), screen printing, flexographic printing, lithographic printing or inkjet printing.

[0053] The non-solvent is selected from the group consisting of benzyl alcohol, benzaldehyde, or a mixture thereof.

[0054] The solvent is selected from the group consisting of ketones, esters, especially cyclic esters, dimethyl sulfoxide, phosphate esters, such as triethyl phosphate, carbonates, ethers, such as tetrahydrofuran, and mixtures thereof; the solvent is preferably selected from the group consisting of ethyl acetate, methyl ethyl ketone, γ-butyrolactone, triethyl phosphate, cyclopentanone, propylene glycol monomethyl ether acetate, and mixtures thereof.

[0055] In one embodiment, the solvent is gamma-butyrolactone and the non-solvent is benzyl alcohol, or the solvent is ethyl acetate and the non-solvent is benzyl alcohol, or the solvent is methyl ethyl ketone and the non-solvent is benzyl alcohol.

[0056] The porous film thus obtained contains pores having an average diameter of 0.1 to 10 μm, preferably 0.2 to 5 μm, and more preferably 0.3 to 4 μm. The average pore diameter can be measured by a scanning electron microscope.

[0057] Regarding the procedures for the actual preparation of the porous membrane, the above approach involves only the preparation of the ink, its deposition and its drying, after which the porous membrane is produced. This method has the advantage that it does not require precipitation from water, compounds which may degrade the performance qualities of the membrane for electronic applications.

[0058] Ion Conductive Oligomers The solid polymer electrolyte according to the present invention comprises an oligomer impregnated into a film of a thermoplastic polymer.

[0059] Oligomers or oligomeric molecules are intermediate compounds between monomers and polymers, whose structure essentially comprises a number of small monomeric units. Oligomers generally have a number of monomeric units in the range of 5 to 100 and / or a number-average molecular mass of less than or equal to 5000 g / mol. The number of monomeric units is usually less than 50, or even 30. The number-average molecular mass may in particular be less than 4000 g / mol, or 3000 g / mol, or even 2000 g / mol.

[0060] This oligomer is an ion conductor, i.e. advantageously has an ion conductivity of at least 0.1 mS / cm at 25° C. in the presence of a Li salt. It must necessarily be in pure liquid form or dissolved in a solvent. According to one embodiment, the ion conductive oligomer has a function of having an affinity for the thermoplastic polymer. According to one embodiment, the oligomer advantageously comprises the group -CR2-O, where R is: H, alkyl, aryl or alkenyl, the preferred group being that of H.

[0061] According to one embodiment, the oligomer has at least one group of the polyethylene glycol (PEG) type. Among these oligomers, methoxypolyethylene glycol methacrylate is advantageous. One of these products, SR 550 from Sartomer, is shown below:

[0062] [ka]

[0063] Solid Polymer Electrolyte The solid polymer electrolyte has sufficient ionic conductivity of at least 0.1 mS / cm at 25°C.

[0064] In addition to the thermoplastic polymer film and oligomer, the solid polymer electrolyte contains one or more lithium salts.

[0065] When the technology is a lithium-based technology, the electrolyte salt dissolved in the oligomer is selected from one or more of the following: lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4); lithium hexafluoroarsenate (LiAsF6); lithium tetrafluoroborate (LiBF4); lithium 4,5-dicyano-2-(trifluoromethyl)imidazol-1-ide (LiTDI); lithium bis(fluorosulfonyl)imide (LiFSI); lithium bistrifluoromethanesulfonimide (LiTFSI); lithium N-fluorosulfonyl-trifluoromethanesulfonylamide (Li-FTFSI); lithium tris(fluorosulfonyl)methide (Li-FSM); lithium bis(perfluoroethylsulfonyl)imide (LiBETI); lithium bis(oxalato)borate (LiBOB); lithium difluoro(oxalato)borate (LiDFOB); lithium 3-polysulfide sulfolane (LiDMDO), or mixtures thereof.

[0066] In the solid polymer electrolyte according to the present invention, the thermoplastic polymer is present in an amount ranging from 10% to 90%, preferably from 20% to 80%, and the oligomer is present in an amount ranging from 90% to 10%, preferably from 80% to 20%, based on the total weight of the solid polymer electrolyte.

[0067] The invention also relates to a method for producing a polymer electrolyte, characterized in that it comprises dissolving a lithium salt in a conductive oligomer and then impregnating a film of a thermoplastic polymer with this solution.

[0068] The thermoplastic polymers may be crosslinked or not crosslinked. In the case of crosslinking, this is carried out thermally using crosslinking agents such as free radical generators, among which azo compounds such as azobisisobutyronitrile (AIBN) or peroxides such as Luperox® 26 can be mentioned.

[0069] The present invention also relates to a separator for a lithium polymer battery, characterized in that it contains the above-mentioned solid polymer electrolyte.

[0070] According to one embodiment, in the separator, the solid polymer electrolyte is deposited on a porous support, such as cellulose, polyolefin or polyacrylonitrile, the thickness of which is between 4 and 50 microns, preferentially between 7 and 35 microns and even more preferentially between 10 and 20 microns.

[0071] According to one embodiment, the separator may also include up to 50% by weight of inorganic particles.

[0072] According to one embodiment, these particles are made of conductive ceramics, such as sulfur-based ceramics Li2S-P2S5 (with a molar ratio of Li2S to P2S5 between 1 and 3) and derivatives thereof, lacunar Li, optionally doped with Al, Ga, Ge or Ba. 3x La 2 / 3-x TiO3 (normal type A II B IV O3) perovskite, Li7La3Zr2O, optionally doped with Ta, W, Al or Ti 12 type garnets, NASICON type LiGe2(PO4)3 or LiTi2(PO4)3 ceramics optionally doped with Ti, Ge, Al, P, Ga or Si, and Li3OCl or Na3OCl type antiperovskites optionally doped with OH or Ba.

[0073] According to one embodiment, these particles are selected from fillers that are essentially non-conductive or essentially very poorly conductive at room temperature, such as silica, alumina, titanium oxide, zirconium oxide, and mixtures thereof.

[0074] According to one embodiment, these particles are selected from fillers having a dielectric constant greater than 2000, such as barium, strontium and lead titanate, lead zirconate, zirconium and lead titanate, and mixtures thereof.

[0075] The separator may contain other additives such as agents that promote the migration of conductive chains, particularly succinonitrile.

[0076] Another subject of the invention is a lithium polymer battery comprising a separator based on a solid polymer electrolyte as defined above, placed between an anode made of lithium metal and a cathode.

[0077] According to another aspect, the invention relates to a lithium battery comprising a stack of layers, said stack comprising an anode, a cathode and a separator predominantly made of lithium metal.

[0078] The cathode consists of: Between 35% and 98% by weight of electrochemically active material. More specifically, the electrochemically active material is selected from at least one of the following materials, but is not limited to: Lithiated iron phosphate (LFP); Lithiated nickel manganese cobalt (NMC) oxide; Lithiated nickel cobalt aluminum (NCA) oxide; Lithiated manganese oxide (LMO); Lithiated nickel manganese (LM) oxide; Lithiated cobalt oxide (LCO), sulfur; or mixtures thereof. To improve electronic conduction, poorly conductive materials such as iron phosphate or manganese phosphate may be coated with a layer of carbon; Between 0.15% and 25% by weight of a conductive additive selected from at least one of the following carbon-based fillers: carbon black; single-wall or multi-wall carbon nanotubes; carbon nanofibers; graphite; graphene; fullerenes; or mixtures thereof; - between 20% and 60% by weight of polymer electrolyte; -Optionally, between 0-5% by weight of a polymer that binds the particles together and improves mechanical strength and adhesion to the current collector, selected from at least one of the following binders: poly(vinylidene fluoride) (PVDF) and its derivatives and copolymers; carboxymethyl cellulose (CMC); styrene butadiene rubber (SBR); poly(ethylene oxide) (PEO); poly(propylene oxide) (PPO); polyglycols; or mixtures thereof.

[0079] The current collector of such cathodes is made from aluminum, carbon-coated aluminum or carbon.

[0080] The anode consists of: - an electrochemically active material that may be treated with lithium metal, graphite, lithiated titanium oxide (LTO), silicon, silicon-carbon composite, or graphene. The active material may be coated with carbon to improve electronic conduction; - a conductive additive present between 0.15% and 25% by weight, selected from at least one of the following carbon-based fillers: carbon black; single-wall or multi-wall carbon nanotubes; carbon nanofibers; graphite; graphene; fullerenes; or mixtures thereof; Between 15% and 60% by weight of polymer electrolyte.

[0081] The current collectors of such anodes are made of copper, carbon or nickel, although Li metal technology envisages the Li foil being its own current collector.

[0082] The conductive additives included in the anode and / or cathode configuration can be selected from carbon-based fillers. According to the present invention, the term "carbon-based filler" refers to a filler containing elements from the group formed by carbon nanotubes, carbon nanofibers, graphene, fullerenes and carbon black, or mixtures thereof in any proportion. According to the present invention, the term "graphene" refers to flat, separated and distinct graphite sheets, but also, by extension, to aggregates containing between one and several tens of sheets and having a flat or more or less wavy structure. This definition therefore includes FLG (Few Layer Graphene), NGP (Nanosized Graphene Plate), CNS (Carbon NanoSheets) and GNR (Graphene NanoRibbons). On the other hand, carbon nanotubes and nanofibers, which are composed of a coaxial roll-up of one or more graphene sheets and turbostratic stacking of these sheets, respectively, and graphite composed of aggregates containing more than several tens of sheets, are excluded.

[0083] Preferably, the carbon-based filler is carbon nanotubes alone or in a mixture with graphene.

[0084] Carbon nanotubes (CNTs) may be of the single-wall type (SWCNTs), double-wall type or multi-wall type (MWCNTs). Double-wall nanotubes are in particular described in Flahaut, E. et al., “Gram-scale CCVD synthesis of double-walled carbon nanotubes.” (2003) Chemical Communications (No. 12) pages 1442-1443. Multi-walled nanotubes, for their part, can be prepared as described in WO 03 / 02456. The nanotubes usually have an average diameter in the range of 0.1 to 100 nm, preferably 0.4 to 50 nm, better still 1 to 30 nm or even 10 to 15 nm, and advantageously have a length of 0.1 to 10 μm. Their length / diameter ratio is preferably greater than 10, usually greater than 100. Their specific surface area is, for example, between 100 and 300 m 2 / g, preferably between 200 and 300 m 2 / g, and their apparent densities are particularly between 0.05 and 0.5 g / cm 3 Between 0.1 and 0.2 g / cm 3 A multi-walled nanotube may for example comprise between 5 and 20 sheets (or walls), more preferentially between 7 and 10 sheets.

[0085] An example of raw carbon nanotubes is notably commercially available under the trade name Graphistrength® C100 from the company Arkema. Alternatively, these nanotubes may be purified and / or treated (for example oxidized) and / or ground and / or functionalized before being used in the method according to the invention. Raw or ground nanotubes may be purified by washing with a sulfuric acid solution in order to free them from residual mineral and metallic impurities. Purification may be carried out by heat treatment at high temperatures (above 2200° C.) under an inert atmosphere. Oxidation of the nanotubes is advantageously carried out by contacting them with a sodium hypochlorite solution or by exposing them to atmospheric oxygen at temperatures between 600 and 700° C. Functionalization of the nanotubes may be carried out by grafting reactive units, such as vinyl monomers, onto the surface of the nanotubes.

[0086] The graphene used can be obtained by chemical vapor deposition or CVD, preferably according to a method using a powder catalyst based on mixed oxides. It is characterized in that it is in the form of particles with a thickness of less than 50 nm, preferably less than 15 nm, more preferentially less than 5 nm, and with submicron lateral dimensions of 10 to 1000 nm, preferentially 50 to 600 nm, more preferentially 100 to 400 nm. Each of these particles generally contains 1 to 50, preferably 1 to 20, more preferably 1 to 10 sheets. Various methods for preparing graphene have been proposed in the literature, including those known as mechanical exfoliation and chemical exfoliation, which consist, respectively, in exfoliating the graphite sheets in successive layers by using adhesive tape (Geim AK, Science, 306: 666, 2004) or by using reagents such as sulfuric acid in combination with nitric acid, intercalating between the graphite sheets and oxidizing the graphite sheets to form graphite oxide, which can be easily exfoliated in water in the presence of ultrasound. Another exfoliation technique consists of subjecting graphite in a dispersion to ultrasound in the presence of a surfactant (US7824651). Graphene particles can also be obtained by cutting carbon nanotubes along their longitudinal axis ("Micro-Wave Synthesis of Large Few-Layer Graphene Sheets in Aqueous Solution of Ammonia", Janowska, I. et al., NanoResearch, 2009 or "Narrow Graphene Nanoribbons from Carbon Nanotubes", Jiao L. et al., Nature, 458: 877-880, 2009). Yet another method of preparing graphene consists of high-temperature decomposition of silicon carbide under vacuum. Finally, some authors have described a method of synthesizing graphene by chemical vapor deposition (CVD), optionally combined with a radio frequency generator (RF-CVD) (Dervishi et al., J. Mater. Sci., 47: 1910-1919, 2012).

[0087] Fullerenes are molecules made entirely or substantially entirely of carbon that can take on geometries resembling spheres, ellipsoids, tubes (known as nanotubes), or rings. Fullerenes can be selected, for example, from C60 fullerenes, C70, which are spherical compounds formed from 60 carbon atoms, PCBM with the formula methyl[6,6]-phenyl-C61-butyrate, and PC71-BM with the formula methyl[6,6]-phenyl-C71-butyrate, which are fullerene derivatives whose chemical structure has been modified to make them soluble.

[0088] Carbon nanofibers, like carbon nanotubes, are nanofilaments produced by chemical vapor deposition (or CVD) starting from carbon-based sources decomposed at temperatures between 500 ° C and 1200 ° C in the presence of hydrogen with a catalyst containing transition metals (Fe, Ni, Co, Cu). Carbon nanofibers are composed of more or less organized graphitic domains (or turbostratic stacks), the planes of which are inclined at variable angles to the axis of the fiber. These stacks can take the form of platelets, fishbones or stacked plates to form structures with diameters generally ranging from 100 nm to 500 nm or more. In the process according to the invention, carbon nanofibers with a diameter of 100 to 200 nm, for example about 150 nm (VGCF (registered trademark) from Showa Denko), advantageously with a length of 100 to 200 μm, are preferred.

[0089] A further carbon-based filler that can be used is carbon black, which is a colloidal carbon-based material produced industrially by incomplete combustion of heavy petroleum products and is in the form of carbon spheres and agglomerates of these spheres, the dimensions of which are generally between 10 and 1000 nm.

[0090] Very advantageously, these conductive additives are added to the composition of each electrode in a content between 0.25% and 25% by weight. EXAMPLES

[0091] The following examples illustrate the invention without limiting it.

[0092] [Example 1] A film of p(VDF-TrFE) copolymer is prepared by dissolving 10 g of Piezotech FC20 copolymer in a solvent mixture consisting of 75 g of γ-butyrolactone and 15 g of benzyl alcohol, then deposited on a glass slide, and the resulting film of 4 cm×2 cm, i.e. 0.0664 g, is dried. This film is then impregnated in a glove box with 0.097 g of SR550 in which 23.1 mg of LiTFSI has been predissolved. This amount corresponds to EO / Li=13.

[0093] In less than 30 seconds, the SR550 is absorbed into the pores. The film is then placed in a 50° C. oven overnight.

[0094] [Example 2] The procedure of Example 1 is repeated for a ratio EO / Li=17.

[0095] [Example 3] The procedure of Example 1 is repeated for a ratio EO / Li=25.

[0096] [Example 4] Ionic conductivity is determined by electrochemical impedance spectroscopy. The material is placed between two stainless steel electrodes (actual thickness approx. 100 μm) inside a leak-proof cell. Film preparation and cell assembly are performed in a glove box under argon atmosphere. The cell is kept at 80 °C for 1 h to ensure good contact between the sample and the stainless steel electrodes. The actual measurements are performed using an EIS Bio-Logic VMP 3 potentiostat / galvanostat with an amplitude of 500 mV between 1 Hz and 1 MHz.

[0097] The values ​​found for the three examples are reported below in Table 1. The values ​​prove to be almost independent of the EO / Li ratio, which is an advantage with regard to industrial extrapolation.

[0098] [Table 1]

[0099] [Example 5] Electrochemical stability represents the ability of the electrolyte to withstand electrochemical decomposition. Electrochemical stability measurements were performed on a 2.01 cm2 sample of the copolymer film prepared according to Example 2. 2 The experiment was carried out at 60° C. in a CR 2032 button cell (two electrodes) using SUS 316 L stainless steel as the working surface with an area of ​​100 μm.

[0100] The electrochemical method used is slow cyclic voltammetry, performed at a sweep rate of 1 mV / s. This method shows the oxidation current as a function of voltage, and whenever the current approaches 0, the operating voltage of the polymer electrolyte is stable. The electrochemical stability is equal to 4.5 V. The curve I=f(V) is completely flat up to 0 V.

Claims

1. 1. A solid polymer electrolyte for a battery operating at a temperature below 60° C., comprising: a thermoplastic polymer in the form of a porous film having a molecular mass of more than 50,000 g / mol; an oligomer, which is an ion conductor, to be impregnated into the film of said thermoplastic polymer; and one or more lithium salts, Electrolytes including:

2. The thermoplastic polymer has the general formula: -[(CR 1 R 2 -CR 3 R 4 )-] n (In the formula, R 1 , R 2 , R 3 and R 4 are independently H, F, CH 3 , Cl, Br or CF 3 and at least one of these groups is F or CF 3 2. The solid polymer electrolyte of claim 1 , wherein

3. 3. The solid polymer electrolyte according to claim 1, wherein the thermoplastic polymer is a fluoropolymer selected from poly(vinylidene fluoride-co-hexafluoropropene), poly(vinylidene fluoride-co-trifluoroethylene), poly(vinylidene fluoride-ter-trifluoroethylene-ter-chlorotrifluoroethylene) and poly(vinylidene fluoride-ter-trifluoroethylene-ter-1,1-chlorofluoroethylene).

4. 4. Solid polymer electrolyte according to claim 1, wherein said thermoplastic polymer is a P(VDF-TrFE) copolymer with a VDF / TrFE molar ratio in the structural units ranging from 9 to 0.1, preferably from 4 to 1.

5. 4. Solid polymer electrolyte according to claim 1, wherein said thermoplastic polymer is a P(VDF-TrFE-CTFE) terpolymer with a molar VDF content ranging from 40% to 95%, a molar TrFE content ranging from 5% to 60% and a molar CTFE content ranging from 0.5% to 20%.

6. The oligomer comprises a group -CR 2 The solid polymer electrolyte according to any one of claims 1 to 5, comprising -O, where R is H, alkyl, aryl or alkenyl.

7. The solid polymer electrolyte of claim 6, wherein the oligomer has at least one group of the polyethylene glycol type.

8. Lithium hexafluorophosphate (LiPF 6 ), lithium perchlorate (LiClO 4 ); lithium hexafluoroarsenate (LiAsF 6 ); lithium tetrafluoroborate (LiBF 4 8. The solid polymer electrolyte of claim 1, comprising one or more lithium salts selected from: lithium 4,5-dicyano-2-(trifluoromethyl)imidazol-1-ide (LiTDI); lithium bis(fluorosulfonyl)imide (LiFSI); lithium bistrifluoromethanesulfonimide (LiTFSI); lithium N-fluorosulfonyl-trifluoromethanesulfonylamide (Li-FTFSI); lithium tris(fluorosulfonyl)methide (Li-FSM); lithium bis(perfluoroethylsulfonyl)imide (LiBETI); lithium bis(oxalato)borate (LiBOB); lithium difluoro(oxalate)borate (LiDFOB); lithium 3-polysulfide sulfolane (LiDMDO), or mixtures thereof.

9. 8. Solid polymer electrolyte according to claim 1, wherein the thermoplastic polymer is present in an amount ranging from 10% to 90%, preferably from 20% to 80%, and the oligomer is present in an amount ranging from 90% to 10%, preferably from 80% to 20%, based on the total weight of the solid polymer electrolyte.

10. A solid polymer electrolyte according to any one of claims 1 to 9, wherein said porous film of a thermoplastic polymer is produced by a method comprising the steps of: providing an ink comprising said thermoplastic polymer and a vehicle comprising a solvent for said polymer and a non-solvent for said polymer, said solvent and said non-solvent being mutually miscible; - depositing said ink on a substrate; - Evaporating the vehicle including the solvent and the non-solvent.

11. A solid polymer electrolyte according to any one of claims 1 to 10, having an ionic conductivity of at least 0.1 mS / cm at 25°C.

12. 12. A solid polymer electrolyte according to claim 1, wherein the pores of the thermoplastic polymer film have an average diameter, measured by scanning electron microscopy, of 0.1 to 10 μm, preferably 0.2 to 5 μm, more preferably 0.3 to 4 μm.

13. Solid polymer electrolyte according to any one of the preceding claims, in which the oligomers have a number-average molecular mass less than or equal to 5000 g / mol, and preferentially less than or equal to 2000 g / mol.

14. A method for producing a solid polymer electrolyte according to one of claims 1 to 13, characterized in that it consists of dissolving said lithium salt in said conductive oligomer and then impregnating said film of thermoplastic polymer with this solution.

15. A separator for a lithium-polymer battery, characterized in that it comprises a solid polymer electrolyte according to one of claims 1 to 13.

16. 16. The separator of claim 15, further comprising up to 50% by weight of inorganic particles, said particles being selected from conductive ceramics, fillers that are essentially non-conductive or very poorly conductive at room temperature, and fillers having a dielectric constant greater than 2000.

17. A lithium-polymer battery comprising an anode made of lithium metal, a cathode and a separator placed between the two electrodes, characterized in that the separator comprises a solid polymer electrolyte according to one of claims 1 to 13.

Citation Information

Patent Citations

  • Total enteral nutrition composition

    WO2008010472A1

  • Method for producing polylactones and polylactams

    WO2008104723A1